Caractérisation spatiale de l’aléa inondation à partir d’images satellites RADAR - Renaud Hostache; Christian Puech; Damien Raclot (Cybergeo)
Spatial characterization is a recurrent problem in flood risk management for which remote sensing data, especially satellite data can be very useful. The general aim of our study is to evaluate contributions of satellite data use and, especially, to develop methods which upgrade RADAR images for spatial characterization of flood hazard. Our study aims to help hydraulic modelling by evaluation of water heights and volumes. The method presented in this paper is composed of three main stages: 1) flood cartography from RADAR images and extraction of informative limits, 2) water levels evaluation in flood plain by matching informative limits with topographic data, 3) decrease of water levels estimation by introduction of hydraulic coherence concept.